The Influence of Service Quality and Brand Image on Customer Loyalty with Company Reputation as a Mediating Variable at Starbucks Indonesia - Wulansari, Triningsih; Arief, Mts.; Poernomo , Henry (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the influence of service quality and brand image on customer loyalty with corporate reputation as a mediating variable at Starbucks Indonesia. The food and beverage industry, particularly the coffee shop business, faces significant challenges in maintaining customer loyalty amidst increasingly intense competition in the post-Covid-19 pandemic era and the Middle East conflict. Starbucks Indonesia, as one of the leading international coffee shop chains, needs to implement adaptive marketing strategies to maintain market position and customer loyalty. This research employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to Starbucks customers in the Jakarta area, with samples selected using purposive sampling. The main variables in this study include service quality (responsiveness, reliability, empathy), brand image, corporate reputation, and customer loyalty. Data analysis was conducted using the Partial Least Squares (PLS) method to evaluate direct and indirect relationships among these variables. The results of the study indicate that service quality has a positive and significant effect on corporate reputation. Similarly, brand image also has a positive and significant influence on corporate reputation. Corporate reputation, in turn, positively contributes to customer loyalty. However, there is a direct negative relationship between service quality and customer loyalty, indicating that customer loyalty is not solely determined by service quality but also by corporate reputation as a mediating factor. Additionally, brand image has both direct and indirect positive effects on customer loyalty through corporate reputation